2013
DOI: 10.14569/ijacsa.2013.040601
|View full text |Cite
|
Sign up to set email alerts
|

A multi-scale method for automatically extracting the dominant features of cervical vertebrae in CT images

Abstract: Abstract-Localization of the dominant points of cervical spines in medical images is important for improving the medical automation in clinical head and neck applications. In order to automatically identify the dominant points of cervical vertebrae in neck CT images with precision, we propose a method based on multi-scale contour analysis to analyzing the deformable shape of spines. To extract the spine contour, we introduce a method to automatically generate the initial contour of the spine shape, and the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…It has also been shown that the developed strategy outperforms the existing local binary fitting model. Identification of dominant features in cervical vertebrae has been reported in [10] which uses the geodesic active contours for extracting the ROI. The initialization is again through Otsu's threshold and a series of morphological operations for eliminating the air path which is shown as small blobs in the thresholded image.…”
Section: Jiyo S Athertya G Saravana Kumar Ieee Membermentioning
confidence: 99%
“…It has also been shown that the developed strategy outperforms the existing local binary fitting model. Identification of dominant features in cervical vertebrae has been reported in [10] which uses the geodesic active contours for extracting the ROI. The initialization is again through Otsu's threshold and a series of morphological operations for eliminating the air path which is shown as small blobs in the thresholded image.…”
Section: Jiyo S Athertya G Saravana Kumar Ieee Membermentioning
confidence: 99%
“…The level set is formulated in terms of intensities by adding a weighted kernel to each pixel, as opposed to [10], where the edge stopping function is defined in terms of Euler Lagrange coefficients. Wu and Lin were able to identify dominant features in cervical vertebrae with a similar thresholdbased initialization approach [11]. To overcome the inherent drawbacks of thresholding, an adaptive 3D region growing method is devised in [12].…”
Section: Introductionmentioning
confidence: 99%